Definition of the relationship between tourism and the concept of “space tourism” - Kozhanazar, А.; Baimbetova, А.; Tleubaeva , А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
Currently, the topic of space tourism has become the subject of discussions by scientists. While some scientists associate space tourism with tourism, some argue that space tourism is not related to tourism. The main reason for the controversy surrounding the concept of “space tourism” is that there is no clear definition of “space tourism.” There are also those who still perceive the concept of space tourism as a futuristic term. All this follows from the fact that measures have not yet been developed to identify the main features of space tourism, its definition has not been clarified and its place in the tourism classification has not yet been determined. To determine whether there is a connection between tourism and space tourism, first of all it is necessary to scrutinize how it corresponds to the existing term “tourism,” taking “space tourism” as a concept. The purpose of this article is to identify the relationship of the concept of “space tourism” with tourism. The discussion section will analyze data from various Western and domestic sources. As a result of desk studies, it is proposed that the definition of “space tourism” fully corresponds to the definition of “tourism” and can be recognized as a type of tourism.